Efficacy of vision therapy in impaired stereoscopic depth with intermittent exotropia (true divergence excess) with unilateral amblyopia: a case report - Gupta, Reena; Jangra, Richa; Dubey, Gaurav; Hooda, Ramesh; Parmar, Nirmal (International Journal Of Community Medicine And Public Health, 2020)
Divergence excess (DE) can be described clinically as exotropia at far greater than the near deviation by at least 10 prism dioptres (PD). We are reporting a rare case of 25-year-old female visited in the eye department for a routine eye check-up with a history of decreased vision in one eye. On examination, it was detected as a case of unilateral amblyopia with intermittent exotropia of true divergence excess with high accommodative-convergence over accommodation (AC/A) ratio. The patient was asymptomatic from exo-deviation due to the presence of binocular vision and good fusional reserve. The patient was started on active conventional vision therapy along with occlusion therapy. Post 16 weeks of constant therapy, a vision assessment with complete squint assessment along with binocular vision tests were performed. The result interprets to support the use of active conventional vision therapy as an integral part of the clinical treatment of amblyopia and intermittent exotropia. The rate of recovery of several monocular functions monitored during the vision therapy period provides the evidence of neural plasticity at multiple sites in the visual pathway in this adult amblyope. Therefore, if an ordered plan is being followed for the management of the patient of unilateral amblyopia and divergence excess, it can yield long-lasting improvement in visual acuity and binocular functions of any age.